Thromboembolic and hemorrhagic risk level in patients with permanent nonvalvular atrial fibrillation - Santaya López, Rolando; Cecilia Paredes, Eduardo Enrique; Echevarría Cruz, Ángel; Sparis Tejido, Mario Manuel; Hidalgo Gato Castillo, Dianelys (SCT Proceedings in Interdisciplinary Insights and Innovations, 2023)
Introduction: atrial fibrillation is the most frequent cardiac arrhythmia in daily clinical practice and is associated with a marked increase in the risk of thromboembolic accidents. Objective: to characterize the level of thromboembolic and hemorrhagic risk in patients with permanent non-valvular atrial fibrillation in the Clinical Surgical Teaching Hospital “Dr. León Cuervo Rubio” of Pinar del Río during the period from July 2017 to July 2019. Material and methods: an observational, descriptive and transversal research was carried out. The universe was studied in its totality and consisted of 80 patients according to established selection criteria. Data were obtained from the review of medical records, and were presented in tables and graphs for a better understanding. Percentage statistical method was used. Results: there was a marked prevalence of patients over 70 years of age (75 %), male sex (65 %) and white skin color (75 %). High thromboembolic risk was predominant (71.25 %) and these patients mainly received anticoagulant treatment. Age (75 5) was the usual risk factor for bleeding according to the HAS-BLED scale. Patients with a high bleeding risk level predominated (52.5 %). Conclusions: most patients had a high thromboembolic risk level and received anticoagulant treatment. The most frequent bleeding risk factors according to the HAS-BLED scale were age, drugs, alcohol and labile INR. Most patients had an elevated bleeding risk level